Catalytic consequences of micropore topology on biomass pyrolysis vapors over shape selective zeolites - Yusup, Suzana (2017)
Research on utilization of abundant rice residue for valuable bioenergy products is still not explored completely. A simple, robust, cheap and one step fast pyrolysis reactor is still a key demand for production of bioenergy products, i.e. high quality bio-oil and bio char.